Automatización del proceso de Riesgo Psicosocial en Pymes (2023)
According to the Ministry of Health, the First National Survey on Health and Work Conditions, conducted in 2007, found that "An adult spends most of their life in a workplace", which can lead to exposure to both physical and psychological risk factors. These working conditions can include ergonomic factors, flexible hours, stress levels, and other factors that occur on a daily basis